2020
DOI: 10.1021/acs.energyfuels.0c02149
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Potential Applications of Hydrochars Derived from P- and N-Enriched Agricultural and Antibiotic Residues via Microwave-Assisted Hydrothermal Conversion

Abstract: The effect of treatment temperature on hydrochars’ properties using P- and N-enriched agricultural and antibiotic residues as feedstocks via microwave-assisted hydrothermal conversion (MW-HTC) was investigated in this study. MW-HTC changed the physicochemical properties of hydrochars, nutrient fractions (phosphorus (P) and nitrogen (N)), and surface functional groups which were characterized by various analysis tools. The N contents in hydrochars derived from rapeseed (RS) and lincomycin (LM) residues were 7.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…161 Likewise, P, N-rich agricultural (rapeseed) and antibiotic (lincomycin) residual feedstocks were used for the preparation of hydrochars via microwave-assisted HTC method for environmental applications. 162…”
Section: Synthesis Methods For Preparation Of Nanoporous Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…161 Likewise, P, N-rich agricultural (rapeseed) and antibiotic (lincomycin) residual feedstocks were used for the preparation of hydrochars via microwave-assisted HTC method for environmental applications. 162…”
Section: Synthesis Methods For Preparation Of Nanoporous Carbonsmentioning
confidence: 99%
“…161 Likewise, P, N-rich agricultural (rapeseed) and antibiotic (lincomycin) residual feedstocks were used for the preparation of hydrochars via microwave-assisted HTC method for environmental applications. 162 The advantages of HTC process over pyrolysis include improved energy consumption, minimized toxic wastes generation, higher yield ($30-60 wt%), retention of surface hydroxyl and carboxylic functional groups and doping of heteroatoms. Even then to meet certain special standards for few applications, template and additive additions are also considered as powerful tools for tuning the pore size ordering and microporosity in the obtained carbon products.…”
Section: Hydrothermal Carbonization (Htc)mentioning
confidence: 99%
“…There are four papers on this topic. Ahmad et al . investigate the effect of the treatment temperature on properties of hydrochars using P- and N-enriched agricultural and antibiotic residues as feedstocks via microwave-assisted hydrothermal conversion.…”
Section: Thermochemical Processes Of Biomassmentioning
confidence: 99%
“…There are four papers on this topic. Ahmad et al 10 investigate the effect of the treatment temperature on properties of hydrochars using P-and N-enriched agricultural and antibiotic residues as feedstocks via microwave-assisted hydrothermal conversion. Huang et al 11 study the effects of torrefaction pressure on the physicochemical properties and combustion characteristics of torrefied Phragmites australis.…”
Section: ■ Thermochemical Processes Of Biomassmentioning
confidence: 99%
“…Although hydrochar has a low surface area and porosity, it can be activated and functionalized by several modification methods, such as CO 2 treatment, the use of KOH or sulfonation with concentrated H 2 SO 4 to improve its physicochemical properties [18][19][20][21]. Therefore, this carbonaceous material has a wide range of applications, having been used in wastewater treatment [22], the removal of heavy metals [18,23], soil amendment [24,25] and energy production [18,25,26]. However, despite the growing interest in hydrochar and its applications, very few studies involving its use in electrochemical sensing have been reported in the literature [27].…”
Section: Introductionmentioning
confidence: 99%